Perencanaan Taman Warga RT. 22 RW. 02 Kecamatan Lebakwangi, Kabupaten Kuningan, Jawa Barat - Bambang Perkasa Alam; Pujiastuti Pujiastuti; Pandhu Pramarta; Edward Alfin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The Community Park Planning Program in RT 22 RW 02, Lebakwangi District, Kuningan Regency, West Java, was designed to develop a functional and sustainable green public space to support social interaction, recreation, and residential environmental quality improvement. The planning process covers site condition analysis, community needs identification, park spatial layout design, vegetation selection, and provision of supporting facilities—including playgrounds, pedestrian pathways, and seating areas—using an eco-friendly approach based on local materials and climate-adaptive plants. Community participation was emphasized across all stages: planning, implementation, and maintenance, in order to build collective ownership of the space. Pre-test and post-test results from 20 respondents recorded a 68% increase in public understanding of green space functions. The program is expected to improve residential environmental quality, strengthen social cohesion among residents, and support the local government's agenda for sustainable green area development in Kuningan Regency.